Using breakout rooms as a teaching strategy to develop English oral production in online classes - Vergara Mendoza, Ketty Zoraida (2022)
Online education is becoming more widely recognized as a tool for educational modernization. Due to the Covid-19 virus, however, this e-learning method began to spread; unknowingly, students and teachers at all levels watched in astonishment as their homes were transformed into classrooms, breaking the entire old system of regular instruction. Through the experiences of students and English teachers, this study intends to examine the impact of breakout rooms on boosting oral English production. This research was done in Unidad Educativa Franciscana San Jose, Milagro Ecuador. It was applied to second and third courses as Technical as science specialization. Based on the shyness and little students’ class participation in the online English classes. The activities were used in the first, second and third parts in the academic year of 2021-2022. In this case, look for a different way to encourage pupils and teachers to use the Zoom platform break out rooms to motivate to better learning and teaching approach. There were many topics based on student’s preferences. A survey with multiple choice and close questions were used to determine the level of satisfaction generated by the interaction in the tasks completed by students in speaking lessons. This work analyses the result of different topics used by teachers to develop oral skill production